Emergency response preparedness for forest fire using the incident command system - Osman, Ahmad Izram (1998)
Most emergency response preparedness problems are not due to failure of the individual. More often, they are system problems. The usual organizational systems (procedures, management structures and designation of responsibilities) established by various organizations to cope with daily and routine emergencies are not well adapted for use in disasters. Experience has shown that no single organizational resource will appropriately serve each and every disaster nor will a single organizational blueprint for emergency planning meet every need. The solution to an effective disaster response lies in the application of sound basic management concepts. Although many systems exist for the command and control of resources in emergency incidents the United State Federal Emergency Management Agency has adopted the Incident Command System as its base for the application of concepts of incident command. The Incident Command System can be adopted by the Fire and Rescue Department Malaysia as an Emergency Response Preparedness for forest fires since this system was originally developed for wildland fire fighting and this system can also be a model for emergency incident management systems to cater for all risks and aid all agencies involved in managing emergencies.